Influences of micro-credit programmes on women empowerment in Bangladesh - Hossain, D; Islam, MA; Majumder, S (Journal of the Bangladesh Agricultural University, 2016)
The focus of this study was to measure the impact of micro-credit programme on women empowerment in Bangladesh. Six leading NGOs/MFIs which operated micro-credit programmes were considered (namely ASA, BRAC, Grameen Bank, SSS, PROSHIKA and TMSS). A total of 406 credit-receivers were randomly selected from twenty-six villages in eight districts of Bangladesh viz., Dhaka, Mymensingh, Sherpur, Netrokona, Kishoregonj, Sylhet, Lalmonirhat, and Narsingdi. The study revealed that 68.5 percent of the respondents could change their empowerment situation. By the estimated change in empowerment it was realised that 15.8 percent of the respondents experienced positive change in their empowerment situation. The main factors affecting the change in women empowerment were membership of different micro-credit organizations, poverty change due to micro-credit and use of loaned money. In single level logistic regression model, the change in poverty situation due to micro-credit had positive association with the perceived change in women empowerment. On the other hand, in multinomial regression analysis the change in poverty situation due to micro-credit had a negative impact on the estimated change in empowerment situation. This contradiction dictates for further investigation into the issue possibly at different component levels of women empowerment. Finally, this research recommended that micro-credit organizations should increase the amount of loan to at least Tk. 15000 encouraging the clients to invest in less risky business with efficient follow up programme. J. Bangladesh Agril. Univ. 14(1): 93-100, June 2016